State Policy, Islamic Knowledge, and Academic Modernization in Malaysian Islamic Higher Education - Roslan, Muhammad Rayyan Hazim bin; Shahril, Haziq Firdaus bin (Jurnal Penelitian Pendidikan Islam, 2026)
This article examines the transformation of Malaysian Islamic higher education within the intersecting dynamics of state policy, Islamic knowledge integration, and academic modernization. Using a qualitative library-based approach, the study analyzes scholarly literature, policy-oriented studies, and institutional discussions related to Islamic higher education governance, curriculum reform, digital transformation, and comparative educational development. The article argues that Malaysian Islamic higher education is neither merely preserving inherited religious traditions nor simply adopting secular models of modernization. Rather, it is undergoing a negotiated transformation shaped by centralized state governance, Islamic epistemology, curriculum integration, financial sustainability, digital innovation, and global academic pressures. The findings show that state policy provides coherence, legitimacy, and regulatory direction, but may also constrain academic autonomy and intellectual plurality. At the same time, the integration of naqli and aqli knowledge, MaqÄá¹£id al-sharÄ«â€˜a-based education, and the mainstreaming of Islamic knowledge offer important foundations for reform. However, these efforts require stronger faculty development, coherent curriculum design, digital capacity, and institutional flexibility. The article contributes an integrated framework for understanding how governance, epistemology, and modernization jointly shape Islamic higher education reform in Malaysia and other Muslim-majority contexts.